Analisis Arahan Pengembangan Kecamatan Sinjai Utara Dalam Mendukung Perkembangan Kabupaten Sinjai - Risnawati K (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2021)
This research is about the Analysis of Development Directions for North Sinjai District in supporting the development of Sinjai Regency. The main problem is How the Direction of North Sinjai District Development Towards the Development of Sinjai Regency. This problem is seen with the physical conditions that arise in supporting the development of sinjai Regency, this study used qualitative descriptive analysis. namely classifying and presenting data in the form of tables, decomposition and pictures and this analysis is carried out to consider the physical conditions that exist in the research location in order to anticipate the development of the North Sinjai District against the development of the Sinjai Regency.